2010
DOI: 10.1016/j.advwatres.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Transport of nonsorbing solutes in a streambed with periodic bedforms

Abstract: Previous studies of hyporheic zone focused largely on the net mass transfer of solutes between stream and streambed. Solute transport processes within the bed has attracted less investigation. In this study, we combined flume experiments and numerical simulations to examine solute transport processes in a streambed with periodic bedforms. Solute originating from the stream was subjected to advective transport driven by pore water circulation due to current-bedform interactions as well as hydrodynamic dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 61 publications
0
105
0
Order By: Relevance
“…Similar simulations could be conducted for streambed ripples. Jin et al (2010) investigated advective-dispersive transport in hyporheic flow caused by bedforms. They found that neglecting dispersion in advection based pumping exchange models can lead to an underestimation of long-term exchange rates and volumes.…”
Section: Heat Exchange and Temperaturementioning
confidence: 99%
“…Similar simulations could be conducted for streambed ripples. Jin et al (2010) investigated advective-dispersive transport in hyporheic flow caused by bedforms. They found that neglecting dispersion in advection based pumping exchange models can lead to an underestimation of long-term exchange rates and volumes.…”
Section: Heat Exchange and Temperaturementioning
confidence: 99%
“…Prior to each experiment, the sand was first thoroughly rinsed with deionized water (four times and 1 h each time) following the method of Jin et al [2010] to remove impurities. It was then washed with salt water of 15 ppt salinity for a sufficiently long time (four times and 1.5 h each time) to ensure that the pore water in the sand had the initial salinity of 15 ppt.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…Additionally, the wall‐normal Reynolds stresses (Figure d) associated with the shear layer are lessened for the dune on a permeable bed (Figure d), and the zone of high Reynolds stress does not impinge on the bed as in the cases for the impermeable bed dunes. Upwelling flow in the leeside can be seen to be supplied by a positive vertical flow within the underlying pores in this region (Figures d, d, and d (bottom)), with subsurface flow downwelling on the stoss side and upwelling in the leeside (Figure d), as has been documented in previous studies of hyporheic flow and bed forms [ Cardenas and Wilson , ; Janssen et al ., ; Hester et al ., ; Thibodeaux and Boyle , ; Jin et al ., ; Harrison and Clayton , ].…”
Section: Resultsmentioning
confidence: 99%
“…However, while progress has been made into refining the original advective pumping model and extending it to more complex geometrical configurations [ Bardini et al ., ; Stonedahl et al ., ], past research has largely neglected the nonlinearity of the turbulent flow above the bed. Recent numerical models typically treat the surface and subsurface flows as separate, assuming turbulent flows above the bed and Darcian flows beneath [ Cardenas and Wilson , , ; Cardenas et al ., ; Jin et al ., ; Janssen et al ., ]. The coupling is obtained through continuity on mean pressure terms, neglecting the existence of a transition region between the two regions, where unsteady and nonlinear interactions are reasonably expected.…”
Section: Introductionmentioning
confidence: 99%